Experiences of healthcare staff providing community-based mental healthcare as a multidisciplinary community mental health team in Central and Eastern Europe findings from the RECOVER-E project: an observational intervention study - Roth, Catharina; Wensing, Michel; Kuzman, Martina Rojnic; Bjedov, Sarah; Medved, Sara; Istvanovic, Ana; Grbic, Danijela Stimac; Simetin, Ivana Pavic; Tomcuk, Aleksandar; Dedovic, Jovo; Djurisic, Tatijana; Nica, Raluca Ileana; et al. (Springer Science and Business Media LLC, 2021)
Community Mental Health Teams (CMHTs) deliver healthcare that supports the recovery of people with mental illness. The aim of this paper was to explore to what extent team members of five CMHTs newly implemented in five countries perceived that they had introduced aspects of the recovery-oriented, strength-based approach into care after a training week on recovery-oriented practice. In addition, it evaluated what the team members' perceptions on their care roles and their level of confidence with this role were.